SIMULATING THE ECONOMIC AND WELFARE IMPACTS OF THE NEW MINIMUM WAGE USING A CGE MODEL - Oluwasola , E Omoju; Ikhide, Emily E (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
This study investigates the economic and welfare impacts of increasing the minimum wage using a static computable general equilibrium (CGE) model calibrated with Nigeria’s updated 2013 social accounting matrix (SAM). The results show that increasing the minimum wage leads to decrease in the demand for labour in most sectors, supporting conventional theory on the impact of minimum wage increase. The results further show that increasing the minimum wage leads to rise in household income, driven by increase in labour income, but the increase in household income is overridden by increase in consumer prices (inflationary pressure), such that the consumption budget of households decline, implying a welfare loss. The welfare loss is higher for urban households than rural households. Lastly, the minimum wage increase results in lower real GDP, suggesting negative impact on the aggregate economy. The study notes that the negative impact of minimum wage increase on labour demand, household welfare and real GDP, is to some extent, mitigated if the government adjusts its expenditure to accommodate the increase.